PENGELOLAAN LIMBAH BENGKEL SEPEDA MOTOR DIKOTA MAKASSAR - Haruna Haruna (UNM Environmental Journals, 2022)
This study aims to find out how the level of mechanical knowledge, mechanical attitude, and pattern of waste management in two-wheeled motorized vehicle workshops in Mamajang and Bontoala Districts, Makassar City. This study uses descriptive methods with quantitative approaches. To achieve the objectives of the study in addition to observations, questionnaires and tests were given to one of the mechanics in each general workshop of two- wheeled vehicles in Mamajang and Bontoala Sub-Districts, Makassar City. The results of the study based on the analysis showed that the mechanics of two-wheeled motorized vehicle workshops in Mamajang and Bontoala Subdistricts tended to have sufficient knowledge, namely, Mamajang Subdistrict of (64%) and Bontola District of (60%). Then the mechanical attitude tends to be in the moderate category, namely Mamajang Subdistrict at (82.2%) and Bontoala District at (85%). Furthermore, the tendency of the behavior of solid waste management conditions in Mamajang District is; do not do the reduction process of (88%), do not carry out the collection process of (72%), do the sorting process by (60%), and do not carry out the utilization process of (72%). Then in Bontoala Subdistrict tends to; do not do the reduction process of (90%), carry out the collection process of (55%), do not do the sorting process by (70%), and do not carry out the utilization process of (75%). Furthermore, the behavior of liquid waste management in Mamajang and Bontoala Subdistricts for the reduction process was not carried out, all mechanics in Mamajang and Bontoala Subdistricts carried out the collection process, the process of sorting out wastewater in the Mamajang Sub-district tend to be 88% and in Bontoala Subdistrict 70%. Then the utilization process in both Mamajang and Botoala Subdistricts tends not to be done. Meanwhile the process of managing gas waste both in Mamajang District and Bontoala was not carried out.